Tagraxofusp as treatment for patients with blastic plasmacytoid dendritic cell neoplasm. Issue 7 (2nd July 2020) - Lee, Sophia S.; McCue, Deborah; Pemmaraju, Naveen
ABSTRACT: Introduction: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare, aggressive hematologic malignancy that previously lacked standardized therapeutic approaches. CD123 (interleukin-3 receptor alpha unit) is highly expressed in many hematologic malignancies, including BPDCN. Tagraxofusp-ezrs (tagraxofusp from herein) is an agent that consists of interleukin-3 fused to a truncated diphtheria toxin, targeting CD123. The Food and Drug Administration recently approved tagraxofusp as therapy for BPDCN for adults and children aged 2 years and older. Areas covered: We discuss the history and clinical background of BPDCN along with tagraxofusp as its first-line therapy. We review the clinical efficacy and safety profile of tagraxofusp in adults including proposed sensitivity and resistance. Finally, we summarize tagraxofusp use in the pediatric population. Expert opinion: Tagraxofusp is a newly approved therapy for BPDCN, a hematologic malignancy that has overall historically poor outcomes. With its significant efficacy, many patients were successfully bridged to stem cell transplantation in the clinical trial leading to its ultimate approval. Clinical awareness for major toxicities, including capillary leak syndrome will be a critical aspect of using this novel agent. In the future, investigation of its use in other hematologic malignancies and expansion of clinical trials in pediatric populations with BPDCN are warranted.